Educational Attainment and Sales Performance in the Insurance Industry: Evidence from AJB Bumiputera 1912 in Palangka Raya - Harjoni, Harjoni (JEMBA: Jurnal Ekonomi Pembangunan, Manajemen & Bisnis, Akuntansi, 2025)
Employee quality remains a critical issue in the life insurance industry, particularly in relation to sales performance and customer acquisition. Educational attainment is often assumed to enhance communication skills, analytical ability, and professional behavior, which are essential for insurance sales agents who interact directly with potential customers. This study examines the effect of educational level on sales performance, measured by customer acquisition and income generation, among sales agents at AJB Bumiputera 1912 in Palangka Raya, Indonesia. A quantitative comparative approach was employed using primary data obtained from company records and field observations. The population consisted of insurance sales agents with senior high school and undergraduate educational backgrounds. A census method was applied to undergraduate agents, while a random sampling technique was used for senior high school agents to ensure equal sample sizes. Data analysis was conducted using non-parametric difference tests to compare average customer acquisition and income between the two educational groups. The results indicate statistically significant differences in both customer acquisition and income levels. Sales agents holding undergraduate degrees demonstrate higher average customer acquisition and greater monthly income compared to those with senior high school education. These findings suggest that higher educational attainment contributes to improved sales effectiveness in the insurance sector through enhanced communication competence, problem-solving ability, and customer engagement. The study provides practical implications for human resource management policies in insurance companies, particularly in recruitment, selection, and incentive system design. Emphasis on educational qualifications may support sustainable sales performance and organizational competitiveness in the long term.